Dynamics of Stochastic Ginzburg-Landau Equations Driven by Colored Noise on Thin Domains (Journal of Nonlinear Modeling and Analysis, 2024)
This work is concerned with the asymptotic behaviors of solutionsto a class of non-autonomous stochastic Ginzburg-Landau equations drivenby colored noise and deterministic non-autonomous terms defined on thin domains. The existence and uniqueness of tempered pullback random attractorsare proved for the stochastic Ginzburg-Landau systems defined on $(n + 1)$-dimensional narrow domain. Furthermore, the upper semicontinuity of theseattractors is established, when a family of $(n + 1)$-dimensional thin domainscollapse onto an $n$-dimensional domain.
Keywords: Stochastic Ginzburg-Landau equation; colored noise; thin domain; random attractor; upper semicontinuity.